Efficient wireless charging transceiver prototype - Shihabuddin Kabashi Khatir Kabashi, 1994-, author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2020)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Elektronik)) - Universiti Teknologi Malaysia, 2020